The Impact of Open Knowledge Maps on Undergraduate Students’ Literature Review Writing in Linguistics - Dewa Ayu Kadek Claria; I Gusti Ngurah Adi Rajistha; A. A. Istri Manik Warmadewi (Balai Bahasa Sulawesi Selatan, 2026)
This research aims to evaluate the impact of Open Knowledge Maps (OKM) on undergraduate students’ literature review writing in linguistics. Literature review is one of the most important academic skills. However, many students face difficulties in finding relevant sources, structuring ideas, and integrating material. This study applies a quasi-experimental design involving undergraduate linguistics students. The participants were assigned to an experimental group using Open Knowledge Maps and a control group using conventional search methods. The data were collected using a pre-test and post-test of literature review writing and supported by an assessment rubric. The results show that students using Open Knowledge Maps achieved significant improvement compared to students in the control group. On statistical analysis there was significant difference between groups (t(66) = 6.89, p .001), with a high effect size (Cohen’s d = 1.63). The findings suggest that visual knowledge mapping may support deeper exploration of academic literature and supports the development of critical academic literacy skills. This research contributes an easily accessible digital tool aimed at helping students improve their research and writing skills, thereby contributing to pedagogical practices in linguistics. AbstrakPenelitian ini bertujuan untuk mengevaluasi dampak Open Knowledge Maps (OKM) terhadap kemampuan penulisan tinjauan pustaka mahasiswa sarjana di bidang linguistik. Tinjauan pustaka merupakan salah satu keterampilan akademik yang paling penting. Namun, banyak mahasiswa mengalami kesulitan dalam menemukan sumber yang relevan, menyusun gagasan, dan mengintegrasikan berbagai materi. Penelitian ini menggunakan desain kuasi-eksperimental yang melibatkan mahasiswa sarjana linguistik. Para peserta dibagi ke dalam kelompok eksperimen yang menggunakan Open Knowledge Maps dan kelompok kontrol yang menggunakan metode pencarian konvensional. Data dikumpulkan melalui pre-test dan post-test penulisan tinjauan pustaka serta didukung oleh rubrik penilaian. Hasil penelitian menunjukkan bahwa mahasiswa yang menggunakan Open Knowledge Maps mengalami peningkatan yang signifikan dibandingkan dengan kelompok kontrol. Berdasarkan analisis statistik, terdapat perbedaan yang signifikan antara kedua kelompok (t(66) = 6.89, p .001), dengan ukuran efek yang tinggi (Cohen’s d = 1.63). Temuan penelitian ini menunjukkan bahwa pemetaan pengetahuan visual berpotensi mendukung eksplorasi literatur akademik yang lebih mendalam serta mengembangkan keterampilan literasi akademik kritis. Penelitian ini memberikan kontribusi berupa alat digital yang mudah diakses untuk membantu mahasiswa meningkatkan keterampilan penelitian dan penulisan mereka, sehingga turut berkontribusi terhadap praktik pedagogis di bidang linguistik.